Maternal tobacco smoking and offspring autism spectrum disorder or traits in ECHO cohorts. Issue 3 (24th February 2022) - Hertz‐Picciotto, Irva; Korrick, Susan A.; Ladd‐Acosta, Christine; Karagas, Margaret R.; Lyall, Kristen; Schmidt, Rebecca J.; Dunlop, Anne L.; Croen, Lisa A.; Dabelea, Dana; Daniels, Julie L.; Duarte, Cristiane S.; Fallin, M. Daniele; et al.
Abstract: Given inconsistent evidence on preconception or prenatal tobacco use and offspring autism spectrum disorder (ASD), this study assessed associations of maternal smoking with ASD and ASD‐related traits. Among 72 cohorts in the Environmental Influences on Child Health Outcomes consortium, 11 had ASD diagnosis and prenatal tobaccosmoking ( n = 8648). and 7 had Social Responsiveness Scale (SRS) scores of ASD traits ( n = 2399). Cohorts had diagnoses alone (6), traits alone (2), or both (5). Diagnoses drew from parent/caregiver report, review of records, or standardized instruments. Regression models estimated smoking‐related odds ratios (ORs) for diagnoses and standardized mean differences for SRS scores. Cohort‐specific ORs were meta‐analyzed. Overall, maternal smoking was unassociated with child ASD (adjusted OR, 1.08; 95% confidence interval [CI], 0.72–1.61). However, heterogeneity across studies was strong: preterm cohorts showed reduced ASD risk for exposed children. After excluding preterm cohorts (biased by restrictions on causal intermediate and exposure opportunity) and small cohorts (very few ASD cases in either smoking category), the adjusted OR for ASD from maternal smoking was 1.44 (95% CI, 1.02–2.03). Children of smoking (versus non‐smoking) mothers had more ASD traits (SRS T‐score + 2.37 points, 95% CI, 0.73–4.01 points), with results homogeneous across cohorts. Maternal preconception/prenatal smoking was consistently associated with quantitative ASD traits and modestly associated with ASD diagnosis among sufficiently powered United States cohorts of non‐preterm children. Limitations resulting from self‐reported smoking and unmeasured confounders preclude definitive conclusions. Nevertheless, counseling on potential and known risks to the child from maternal smoking is warranted for pregnant women and pregnancy planners. Lay Summary: Evidence on the association between maternal prenatal smoking and the child's risk for autism spectrum disorder has been conflicting, with some studies reporting harmful effects, and others finding reduced risks. Our analysis of children in the ECHO consortium found that maternal prenatal tobacco smoking is consistently associated with an increase in autism‐related symptoms in the general population and modestly associated with elevated risk for a diagnosis of autism spectrum disorder when looking at a combined analysis from multiple studies that each included both pre‐ and full‐term births. However, this study is not proof of a causal connection. Future studies to clarify the role of smoking in autism‐like behaviors or autism diagnoses should collect more reliable data on smoking and measure other exposures or lifestyle factors that might have confounded our results.